Peer review analysis in the field of radiation oncology: results from a web-based survey of the Young DEGRO working group - Käsmann, Lukas; Schröder, Annemarie; Frey, Benjamin; Fleischmann, Daniel F.; Gauer, Tobias; Ebert, Nadja; Hecht, Markus; Krug, David; Niyazi, Maximilian; Mäurer, Matthias (Strahlentherapie und Onkologie, 2020)
Purpose: To evaluate the reviewing behaviour in the German-speaking countries in order to provide recommendations to increase the attractiveness of reviewing activity in the field of radiation oncology. Methods: In November 2019, a survey was conducted by the Young DEGRO working group (jDEGRO) using the online platform “eSurveyCreator”. The questionnaire consisted of 29 items examining a broad range of factors that influence reviewing motivation and performance. Results: A total of 281 responses were received. Of these, 154 (55%) were completed and included in the evaluation. The most important factors for journal selection criteria and peer review performance in the field of radiation oncology are the scientific background of the manuscript (85%), reputation of the journal (59%) and a high impact factor (IF; 40%). Reasons for declining an invitation to review include the scientific background of the article (60%), assumed effort (55%) and a low IF (27%). A double-blind review process is preferred by 70% of respondents to a single-blind (16%) or an open review process (14%). If compensation was offered, 59% of participants would review articles more often. Only 12% of the participants have received compensation for their reviewing activities so far. As compensation for the effort of reviewing, 55% of the respondents would prefer free access to the journal’s articles, 45% a discount for their own manuscripts, 40% reduced congress fees and 39% compensation for expenses. Conclusion: The scientific content of the manuscript, reputation of the journal and a high IF determine the attractiveness for peer reviewing in the field of radiation oncology. The majority of participants prefer a double-blind peer review process and would conduct more reviews if compensation was available. Free access to journal articles, discounts for publication costs or congress fees, or an expense allowance were identified to increase attractiveness of the review process.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Impact factor; Peer review; Publication; Radiation oncology; Scientific publishing